Physical Fitness Survey of Men's Football UKM Students at Muhammadiyah University of Bangka Belitung - Mahrul; Andriadi; Adi Saputra (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
This research was motivated due to the students’ problems including frequent injuries and excessive fatigue during tournaments and practice. It is caused by unstable student physical fitness, which affects game performance. The purpose of this study was to determine the physical fitness of students who joined UKM football at Universitas Muhammadiyah Bangka Belitung. The benefit of this research was as a consideration for trainers which can be used as the reference for students. The type of this research was quantitative descriptive research. The variable in this study was a single variable, namely physical fitness. The sample in this study used a saturated sample of the population while the population of this study were 27 students of UKM football at Universitas Muhammadiyah Bangka Belitung. The results of this study showed that there were 11 students in the good category, there were 16 students in the medium category, while there were 0 students in the very good, poor and very poor categories. Based on the results study, the level of physical fitness of male students who joined UKM football at Universitas Muhammadiyah Bangka Belitung is in the moderate category.